A Significant Addition of Left Ventricular Fractional Shortening to Ejection Fraction correlated with Global Longitudinal Strain Value in Predicting Major Acute Cardiovascular Event in patients with Acute Coronary Syndrome - Bertha Gabriela Napitupulu; Harris Hasan; Nizam Z Akbar; Andre Pasha Ketaren; Zainal Zafri; Ali Nafiah Nasution (The Indonesian Heart Association, 2020)
Background: Global longitudinal strain (GLS) was a proven predictor of systolic function improvement and myocardial remodeling after acute coronary syndrome (ACS) for a residual left ventricular function defined their prognosis. However, not all echocardiography devices are equipped by speckle tracking (STE) as compare to the availability of M-mode modality which capable on assessing fractional shortening (FS) instead. Methods: This study evaluated clinical and echocardiography parameters on myocardial infarction (MI) and non-MI ACS patients. Clinical outcome was defined as composite major acute cardiovascular event (MACE) on 6 months of follow up. Results: Over 145 patients, GLS>-9.4% was found to be an independent predictor of MACE despite of troponin, age, ejection fraction (EF), prior reperfusion and infarct location [(HR 5.89 (1.82-16.51)]. There is negative correlation between FS and GLS (Spearman r -0,717; p<0,01). By using logistic regression analyses, it was found that the addition of FS<25% to biplane Simpson EF<50% could be useful to rule in the presence of GLS>-9.4% (AUC 0.831). Conclusion: GLS had a prognostic value in patients with ACS. Left ventricular conventional M-mode FS in addition to Simpson EF were well correlated with GLS as well they can be considered as an alternative in predicting the incident of MACE in patient with ACS. Keywords: global longitudinal strain, prognostic, fractional shortening, acute coronary syndrome